Fibrinogen Concentrate in Cardiovascular Surgery: A Meta-analysis of Randomized Controlled Trials. (September 2018) - Li, Jing-Yi; Gong, Junsong; Zhu, Fang; Moodie, Jessica; Newitt, Amy; Uruthiramoorthy, Lavanya; Cheng, Davy; Martin, Janet
Abstract : BACKGROUND: Postoperative bleeding remains a frequent complication after cardiovascular surgery and may contribute to serious morbidity and mortality. Observational studies have suggested a relationship between low endogenous plasma fibrinogen concentration and increased risk of postoperative blood loss in cardiac surgery. Although the transfusion of fibrinogen concentrate has been increasing, potential benefits and risks associated with perioperative fibrinogen supplementation in cardiovascular surgery are not fully understood. METHODS: PubMed, Cochrane Library, Ovid MEDLINE, Embase, Web of Science, and China National Knowledge Infrastructure were searched on January 15, 2017, with automated updates searched until February 15, 2018, to identify all randomized controlled trials (RCTs) of fibrinogen concentrate, whether for prophylaxis or treatment of bleeding, in adults undergoing cardiovascular surgery. All RCTs comparing fibrinogen infusion versus any other comparator (placebo/standard of care or another active comparator) in adult cardiovascular surgery and reporting at least 1 predefined clinical outcome were included. The random-effects model was used to calculate risk ratios and weighted mean differences (95% confidence interval [CI]) for dichotomous and continuous variables, respectively. Subgroup analyses by fibrinogen dose and by baseline risk for bleeding were preplanned. RESULTS: A total of 8 RCTs of fibrinogen concentrate in adults (n = 597) of mixed risk or high risk undergoing cardiovascular surgery were included. Compared to placebo or inactive control, perioperative fibrinogen concentrate did not significantly impact risk of all-cause mortality (risk ratio, 0.41; 95% CI, 0.12–1.38; I 2 = 10%; P = .15). Fibrinogen significantly reduced incidence of allogeneic red blood cell transfusion (risk ratio, 0.64; 95% CI, 0.49–0.83; I 2 = 0%; P = .001). No significant differences were found for other clinical outcomes. Subgroup analyses were unremarkable when analyzed according to fibrinogen dose, time of infusion initiation, mean cardiopulmonary bypass time, and rotational thromboelastometry/fibrinogen temogram use (all P values for subgroup interaction were nonsignificant). CONCLUSIONS: Current evidence remains insufficient to support or refute routine perioperative administration of fibrinogen concentrate in patients undergoing cardiovascular surgery. Fibrinogen concentrate may reduce the need for additional allogeneic blood product transfusion in cardiovascular surgery patients at high risk or with evidence of bleeding. However, no definitive advantage was found for reduction in risk of mortality or other clinically relevant outcomes. The small number of clinical events within existing randomized trials suggests that further well-designed studies of adequate power and duration to measure all-cause mortality, stroke, myocardial infarction, reoperation, and thromboembolic events should be conducted. Future studies should also address cost-effectiveness relative to standard of care.